1996
DOI: 10.1111/j.1440-1827.1996.tb03618.x
|View full text |Cite
|
Sign up to set email alerts
|

APC, K‐ras codon 12 mutations and p53 gene expression in carcinoma and adenoma of the gall‐bladder suggest two genetic pathways in gall‐bladder carcinogenesis

Abstract: Current histopathological evidence suggests that gall-bladder cancer has two main morphological pathways for its development: de novo (ab initio) origin and adenoma-carcinoma sequence. In order to investigate the genetic difference between them, APC mutations were examined by RNase protection analysis, K-ras mutations by nested polymerase chain reaction-restriction fragment length polymorphism analysis, and p53 gene overexpression by immunohisto-chemical analysis in both tumors and benign lesions of the gall-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…The minimum overlapping region was 12p12, which corresponds to the chromosomal locus of the K-ras gene (12p12.1). Although it is well known that K-ras mutation is frequent in biliary tract cancers [3, 4, 5, 6, 7, 8], there are only a few reports of K-ras gene amplification in cancers [28, 29]. Accordingly, it is likely that the gain at 12p12 is attributable to an increase in the copy number of gene(s) other than K-ras in biliary tract cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The minimum overlapping region was 12p12, which corresponds to the chromosomal locus of the K-ras gene (12p12.1). Although it is well known that K-ras mutation is frequent in biliary tract cancers [3, 4, 5, 6, 7, 8], there are only a few reports of K-ras gene amplification in cancers [28, 29]. Accordingly, it is likely that the gain at 12p12 is attributable to an increase in the copy number of gene(s) other than K-ras in biliary tract cancer.…”
Section: Discussionmentioning
confidence: 98%
“…However, existing genetic information concerning biliary tract cancers is very limited, although several genes, such as K-ras [3, 4, 5, 6, 7, 8], p53 [8, 9, 10, 11]and c-erbB-2 [11, 12, 13], have been reported to be involved in the development and/or progression of biliary tract cancers. Frequent inactivation of p16 INK4 /CDKN2 and loss of heterozygosity at 3p, 5p and 9p have also been shown in biliary tract cancers [7, 9].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the preoperative diagnostic rate in biliary malignancy, many assays to detect genetic alternations have been investigated, including p53, 12-15 K-ras, [16][17][18][19][20] and telomerase. 21 A group of centrosome abnormalities, detected in cells obtained from the bile or pancreatic juice, could be another modality for the biological diagnosis of biliary malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent evidence from a variety of other cancer models has indicated that telomere shortening may also contribute to carcinoma progression, although this has not been previously examined in biliary tract carcinoma. [10][11][12] For example, telomere shortening appears to be an early and common event in precursors to invasive prostatic and pancreatic cancer.…”
mentioning
confidence: 99%